Size, taxonomic and biomass distributions of flying insects in Central Amazonia: Forest edge vs. understory - Fowler, H. G.; Silva, C. A.; Venticinque, E. (Revista de Biologia Tropical, 1993)
Significantly more individuals and biomass of flying insects were present at the forest edge than in the understory throughout the year, as monitored by flight interception traps, in Central Amazonia. Numbers and biomass of flying insects increased at higher rates at the edge with rainfall, associated with termite swarming behavior and increased Homopteran density. The most abundant insects were Diptera, Coleoptera, Hymenoptera and Isoptera, whose ranked abundances varied with respect to forest edge and understory, as well as with season.
Keywords: AMAZON FOREST; INSECT; DENSITY; BIOMASS EDGE; UNDERSTORY